1995
DOI: 10.1002/j.2161-1912.1995.tb00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing Biracial Ethnic Identity: A Review of the Increasing Dilemma

Abstract: This article describes the current status of biracial youth in the United States. A major purpose is to enhance readers' awareness of the existence of this population and its increasing numerical significance. Models of identity development are presented and relevant sociocultural issues are discussed. In addition, examples of biracial‐specific strategies and interventions are offered for consideration by helping professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 13 publications
0
59
0
Order By: Relevance
“…They also noted that the children rarely reported feeling pressure to 'choose' one identity over another-a common theme in the biracial development literature discussed earlier (Herring, 1995). Overall, the authors concluded that the study's children showed evidence of holding a dual ethnic or cultural identity, as they seemed to culturally identify with the dominant culture, but also self-describing themselves based on their birth ethnicity.…”
Section: Research On Biculturalism In Tra/icamentioning
confidence: 80%
See 4 more Smart Citations
“…They also noted that the children rarely reported feeling pressure to 'choose' one identity over another-a common theme in the biracial development literature discussed earlier (Herring, 1995). Overall, the authors concluded that the study's children showed evidence of holding a dual ethnic or cultural identity, as they seemed to culturally identify with the dominant culture, but also self-describing themselves based on their birth ethnicity.…”
Section: Research On Biculturalism In Tra/icamentioning
confidence: 80%
“…However, some researchers have argued that biracial children often lack access to one or another of their racial groups, and instead they are often forced to "choose" one over another (Herring, 1995;Williams, 1999). In that case, this author argues that the child would be biologically biracial, but not bicultural-a distinction all but absent from the literature.…”
Section: Bicultural and Biracial Identitymentioning
confidence: 99%
See 3 more Smart Citations